The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1113/jphysiol.1993.sp019693
|View full text |Cite
|
Sign up to set email alerts
|

A relay for input from group II muscle afferents in sacral segments of the cat spinal cord.

Abstract: SUMMARY1. A neuronal relay for input from group II afferents of hindlimb muscle nerves has been found in the previously little explored sacral segments of the cat spinal cord.2. Electrical stimulation of group II muscle afferents of a number of nerves evoked negative potentials on the surface (cord dorsum potentials) and population postsynaptic potentials (field potentials) within the sacral segments. The largest potentials were evoked by stimulation of the posterior biceps-semitendinosus and triceps surae ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
48
1

Year Published

1993
1993
1998
1998

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 51 publications
9
48
1
Order By: Relevance
“…The interneurones were located in the dorsal horn, predominantly in the lateral half of laminae IV and V of Rexed (1954), as indicated in Fig. lA-C (Jankowska & Riddell, 1993b). In accordance with these observations, when several (7-10) different ipsilateral muscle nerves were investigated for their effects on sacral interneurones, group II afferents of the PBST nerve appeared to be the main source of input.…”
Section: Methods Preparationsupporting
confidence: 62%
See 4 more Smart Citations
“…The interneurones were located in the dorsal horn, predominantly in the lateral half of laminae IV and V of Rexed (1954), as indicated in Fig. lA-C (Jankowska & Riddell, 1993b). In accordance with these observations, when several (7-10) different ipsilateral muscle nerves were investigated for their effects on sacral interneurones, group II afferents of the PBST nerve appeared to be the main source of input.…”
Section: Methods Preparationsupporting
confidence: 62%
“…We have recently reported that neurones relaying segments, several types of neurones have input from group information from group II muscle afferents are located not II afferents; these include last order interneurones with only rostral, as previously found by Edgley & Jankowska excitatory and inhibitory actions on motoneurones (1987a), but also caudal to the lumbosacral enlargement (Cavallari, Edgley & Jankowska, 1987), other interneurones (Jankowska & Riddell, 1993b), i.e. both in midlumbar and (Edgley & Jankowska, 1987b) and ascending tract neurones in sacral segments of the spinal cord.…”
mentioning
confidence: 91%
See 3 more Smart Citations